A high entropy composite coating for cemented carbide tools and preparation method thereof
By surfacing the FeCoCrNiMn layer of high-entropy alloy on the surface of the cemented carbide tool and performing boron-permeable treatment, the existing rotary tillage tool has been solved, the hardness and friction resistance of the tool are improved, the service life is extended and the production cost is reduced.
Patent Information
- Application Number
- CN202310259128.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The existing rotary tillage tools have poor thermal conductivity, poor wear resistance, high hardness, low life, high brittleness, and insufficient interface bonding strength, resulting in short service life and high production costs.
Through surfacing technology, a high-entropy alloy FeCoCrNiMn layer is formed on the surface of the cemented carbide tool, and a high-entropy alloy boride layer is formed on its surface through the boron-permeable process, which enhances interlayer bonding force and tool hardness and improves anti-friction performance.
It significantly improves the hardness and anti-friction performance of the tool, extends the service life and reduces production costs.
Smart Images

Figure CN116240545B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal coatings, and in particular to a high entropy composite coating for cemented carbide cutting tools and a preparation method thereof. Background Art
[0002] Rotary tillers play an important role in my country's agricultural tools. They can quickly complete rotary tillage operations and improve the efficiency before sowing in dry land. Since the main component of a rotary tiller is a rotary blade, the cost of replacing the rotary blade is high, and it is difficult to meet the long-term domestic use requirements for the rotary blade. As one of the key components of a rotary tiller, the soil-contacting component has a complex working environment and generates a lot of heat due to intense friction. The rotary blade transmits mechanical power through the rotary tiller, so that the tool is quickly screwed into the surface soil layer, and then the cultivated land is turned over. The rotary blade has high working intensity, severe wear, and a short service life. The most important of these is the existence of tool breakage and wear behavior. Improving the wear resistance of the rotary blade is the main method to increase the service life of the soil-contacting tool. The currently used tools have poor thermal conductivity, poor wear resistance, high hardness, low life, and large brittleness. There are also certain deficiencies in the interface bonding strength. Summary of the invention
[0003] The present invention provides a high entropy composite coating for cemented carbide tools and a preparation method thereof. A high entropy alloy FeCoCrNiMn layer is formed on the surface of the cemented carbide tool by surfacing technology, and then a high entropy alloy boride layer is formed on the surface of the high entropy alloy FeCoCrNiMn layer by a boronizing process. Surfacing and boronizing process technologies ensure interlayer bonding, and the high entropy alloy layer has a high Mn content, and there is work hardening, which increases the hardness of the tool. The boronized layer is subjected to impact loads and there is abrasive wear. The addition of the boronized layer greatly increases the anti-friction performance of the soil-contacting component, and the high entropy alloy layer can directly play a high hardness support role on the upper boronized coating, further increasing the anti-friction performance. It is suitable for strengthening soil-contacting components, reducing abrasive wear, so as to increase service life and reduce production costs.
[0004] The solution of the present invention to solve the above technical problems is as follows: a high entropy composite coating for cemented carbide tools, the coating comprising a high entropy alloy FeCoCrNiMn layer coated on the surface of the tool and a high entropy alloy boride layer coated on the surface of the high entropy alloy FeCoCrNiMn layer.
[0005] Preferably, the composition of the high entropy alloy FeCoCrNiMn layer includes, by mass percentage, Fe: 50-60%, Co: 10-20%, Cr: 10-15%, Ni: 10-15%, and Mn: 10-20%; the raw materials of the high entropy alloy boride layer include silicon carbide and ferroboride, wherein the mass ratio of ferroboride to silicon carbide is 1:12-20.
[0006] Preferably, the thickness of the high entropy alloy FeCoCrNiMn layer is 1.0-2.0 mm; the thickness of the high entropy alloy boride layer is 20-30 μm.
[0007] Preferably, the composition of the high entropy alloy FeCoCrNiMn layer includes, by mass percentage, Fe: 55.8%, Co: 11.2%, Cr: 10.9%, Ni: 10.2%, and Mn: 11.9%; the raw materials of the high entropy alloy boride layer include silicon carbide and ferroboron alloy, wherein the mass ratio of ferroboron alloy to silicon carbide is 1:15; the thickness of the high entropy alloy FeCoCrNiMn layer is 2.0 mm; the thickness of the high entropy alloy boride layer is 21.35 μm.
[0008] A method for preparing a high entropy composite coating for a cemented carbide tool as described above comprises the following steps:
[0009] 1) Pre-treat the surface of the carbide tool matrix to increase the bonding force; the specific steps are to grind the surface of the tool matrix with sandpaper of mesh size 180#, 400#, and 800#, respectively, and use alcohol and acetone to clean the surface of the tool matrix for 10-30 minutes in turn to remove the oxide layer and oil and other impurities formed by the long-term contact between the tool matrix surface and the air:
[0010] 2) Screening the high entropy alloy FeCoCrNiMn powder to remove large particles of 200-300 mesh, and drying the powder sample for 20 minutes to remove residual moisture; heating the cemented carbide tool substrate to a set temperature of 300° C.; the composition of the high entropy alloy FeCoCrNiMn powder includes Fe: 50-60%, Co: 10-20%, Cr: 10-15%, Ni: 10-15%, and Mn: 10-20% by mass percentage;
[0011] 3) Under the protection of high-purity argon, the high-entropy alloy FeCoCrNiMn powder is used as welding powder to perform surfacing welding on the cemented carbide tool substrate. After the surfacing welding is completed, the tool substrate is placed in thermal insulation cotton for 30-60 minutes to form a high-entropy alloy FeCoCrNiMn layer on the surface of the cemented carbide tool substrate;
[0012] 4) The surface of the tool substrate with the surfacing high entropy alloy FeCoCrNiMn layer obtained in step 3) is pretreated to increase the bonding force; the specific steps are: using 360#, 600#, and 800# SiC water sandpaper to grind the surface of the tool substrate with the surfacing high entropy alloy FeCoCrNiMn layer step by step, and mechanically polishing with a diamond spray polishing agent with a particle size of 0.5μm, cleaning the surface with alcohol acetone for 10-30min, and drying.
[0013] 5) Boron iron alloy and silicon carbide were mixed evenly in a mass ratio of 1:12-20 as a penetrant, and a HBT-100K vacuum infiltration furnace was used with a vacuum degree of 1.33×10 -3 Pa, under the protection of high-purity argon, the tool substrate with the cladding high-entropy alloy FeCoCrNiMn layer is kept at 800-1200℃ for 8-10h for boronizing; after the boronizing is completed, it is quenched and cooled to room temperature, and the temperature is increased for tempering, cooling, and cleaning, and a high-entropy alloy boride layer is formed on the surface. Quenching treatment improves the organizational properties, enhances wear resistance and fatigue strength; tempering treatment improves organizational stability and eliminates internal stress.
[0014] Preferably, in step 3), a DML-V02BD plasma surfacing machine is used, and surfacing is performed specifically by plasma arc surfacing method, and linear reciprocating welding is set as the surfacing path, the speed is 800-1200 mm / min, the number of reciprocating times is 10-18, more preferably 15 times, and the surfacing arc current is 50-70A.
[0015] Preferably, in step 3), the powder feeding flow rate of the welding powder is 1.5-2.5 L / min.
[0016] Preferably, in step 3), the weld between the tool substrate and the high entropy alloy FeCoCrNiMn layer is processed by continuous welding during the surfacing process, and the weld length is set to 40-60 mm and the weld width is set to 2-4 mm. More preferably, the weld length is set to 50 mm and the weld width is set to 3 mm.
[0017] Preferably, in the step 3), a safety distance of 1-5 mm is reserved between the operating table of the plasma welding machine and the tool base, the overlap rate is set to 30-60%, and the nozzle and the tool base are 10-18 mm apart; further preferably, a safety distance of 2 mm is reserved between the operating table and the tool base, the overlap rate is set to 30-60%, and the nozzle and the base are 15 mm apart.
[0018] Preferably, in step 5), the holding temperature of tempering is 400-450° C., and the duration is 3-4 h; further preferably, in step 5), the holding temperature of tempering is 410° C., and the duration is 3 h.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention forms a high entropy alloy FeCoCrNiMn layer on the surface of the rotary blade through a surfacing welding technology, and then forms a high entropy alloy boride layer on the surface of the high entropy alloy FeCoCrNiMn layer through a boriding process. The surfacing layers are metallurgically bonded through the interface, and the solid boriding layers are grown in situ, thereby ensuring the interlayer bonding strength between the coating and the substrate.
[0021] 2. The high entropy alloy layer has a higher Mn content, which causes work hardening to increase the hardness of the tool. The high entropy alloy layer supports the high entropy boride layer. The borided layer is subjected to impact loads, resulting in abrasive wear, increased wear resistance, reduced wear, and reduced adverse effects of impact under complex working conditions.
[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 This is a schematic diagram of the tool coating structure in Example 1 of the present invention;
[0025] Figure 2 This is a scanning electron micrograph of the boronized layer in the tool coating in Example 1 of the present invention;
[0026] Figure 3 This is a wear scar image of the tool coating after wear in Example 1 of the present invention;
[0027] Figure 4 This is a graph showing the nanoindentation test of the tool coating in Example 1 of the present invention.
[0028] In the accompanying drawings, the components represented by the reference numerals are as follows:
[0029] 1. Tool substrate; 2. High entropy alloy FeCoCrNiMn layer; 3. High entropy alloy boronized layer. DETAILED DESCRIPTION
[0030] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0031] The components of the high entropy alloy FeCoCrNiMn powder used in the following embodiments and comparative examples include Fe: 55.8%, Co: 11.2%, Cr: 10.9%, Ni: 10.2%, and Mn: 11.9% by mass percentage; the boronizing agent is a mixture of silicon carbide and ferroboron alloy, wherein the mass ratio of silicon carbide to ferroboron alloy is 1:15.
[0032] Example 1
[0033] 1. Pretreatment of tool substrate 1: Grind the substrate surface with 180#, 400#, and 800# sandpaper respectively, and clean the substrate surface with alcohol and acetone for 10-30 minutes to remove the oxide layer and oil stains formed by long-term contact between the substrate surface and the air:
[0034] 2. Preparing for surfacing: Screen the high entropy alloy FeCoCrNiMn powder to remove large particles of 200-300 mesh, and dry for 20 minutes to remove residual moisture. Use a small heater device to heat the tool substrate 1 to 300°C.
[0035] 3. Overlay welding of high entropy alloy FeCoCrNiMn layer 2: Use DML-V02BD plasma overlay welding machine, using high-purity Ar 2 As a protective gas, the tool substrate 1 is surfacing welded. Set the automatic powder feeding and powder feeding flow rate to 2.0L / min. Select ion welding as the welding mode, and set the surfacing arc current to 60A; set linear reciprocating welding as the surfacing path, the speed is 800mm / min, and the number of reciprocations is 15 times. The weld is processed by continuous welding, and the weld length is set to 50mm and the width is 3mm. A 2mm safety distance is reserved between the operating table and the tool substrate. The overlap rate is set to 40%, and the nozzle and the substrate are 15mm apart. After the surfacing is completed, the sample is quickly placed in the thermal insulation cotton for 30-60min, that is, a high-entropy alloy FeCoCrNiMn coating 2 with a thickness of 2mm is formed on the surface of the tool substrate.
[0036] 4. Boriding pretreatment: The tool substrate prepared in step 3 is ground step by step using 360#, 600#, and 800# SiC water sandpaper, and mechanically polished with a diamond spray polishing agent with a particle size of 0.5μm. The surface is cleaned with alcohol acetone for 10-30 minutes and dried.
[0037] 5. Forming a high entropy alloy boronized layer: The tool substrate coated with the high entropy alloy layer obtained in step 4 is subjected to a HBT-100K vacuum infiltration furnace, SiC and ferroboron alloy are used as infiltrants, and the temperature is kept at 900°C for 8 hours, quenched and cooled to room temperature, and then heated to 410°C for 3.0 hours for tempering treatment, and then washed after cooling. That is, a high entropy alloy boronized layer 3 with a thickness of 21.35μm is formed on the high entropy alloy FeCoCrNiMn coating.
[0038] Comparative Example 1
[0039] 1. Pretreatment of tool substrate: Grind the substrate surface with 180#, 400#, and 800# sandpaper respectively, and use alcohol and acetone to clean the substrate surface for 10-30 minutes to remove the oxide layer and oil stains formed by long-term contact between the cemented carbide surface and the air:
[0040] 2. Preparing for surfacing: Screen the high entropy alloy FeCoCrNiMn powder to remove large particles of 200-300 mesh, dry the powder for 20 minutes to remove residual moisture. Use a small heater to heat the tool substrate to 300℃.
[0041] 3. Overlay welding of high entropy alloy FeCoCrNiMn layer: DML-V02BD plasma overlay welding machine is used, using high-purity Ar 2 As a protective gas, the tool substrate is surfacing welded. Set the automatic powder feeding and powder feeding flow rate to 2.0L / min. Select ion welding as the welding mode, and set the surfacing arc current to 60A. Set linear reciprocating welding as the surfacing path, the speed is 800mm / min, and the number of reciprocations is 15 times. The weld is processed by continuous welding, the welding powder length is set to 50mm, the width is set to 3mm, and a 2mm safety distance is reserved between the operating table and the tool substrate. The overlap rate is set to 40%, and the nozzle and the substrate are 15mm apart. After the surfacing is completed, the sample is quickly placed in the thermal insulation cotton for 30-60min, that is, a high entropy alloy FeCoCrNiMn coating is formed on the surface of the tool substrate.
[0042] Comparative Example 2
[0043] 1. Pretreatment of tool substrate: Grind the substrate surface with 180#, 400#, and 800# sandpaper respectively, and use alcohol and acetone to clean the substrate surface for 10-30 minutes to remove the oxide layer and oil stains formed by long-term contact between the cemented carbide surface and the air:
[0044] 2. Forming a boronized layer: The tool substrate prepared in step 1 is subjected to a HBT-100K vacuum infiltration furnace, SiC and ferroboron alloy are used as infiltrating agents, and is kept at 900°C for 8 hours, quenched and cooled to room temperature, and then heated to 410°C and kept for 3.0 hours for tempering. After cooling, it is washed to remove the boronizing agent on the coating surface, and a high entropy alloy boronized layer is formed on the surface of the tool substrate.
[0045] The following tests were performed on the surface treated cutting tools of Example 1, Comparative Examples 1 and 2. The test results are shown in Table 1:
[0046] Hardness test: The test was conducted by continuous stiffness measurement (CSM) using a nanoindenter (G200, Agilent technologies, USA). The indenter was a diamond Berkovich tetrahedron indenter with a tip roundness of less than 20 nanometers. The maximum load was 500 mN, and the load resolution was 50 nN. The displacement resolution was less than 0.01 nm. Electromagnetic actuation was used and a capacitive sensor was used for measurement. The nanoindentation test curve of Example 1 is shown in Figure 2. Figure 4 shown.
[0047] Friction coefficient test: The friction and wear test was conducted using a multifunctional friction tester (RTEC MFT-5000). The friction test was conducted in a reciprocating sliding mode with a frequency of 5 Hz and a load of 5 N for 15 minutes. The sliding distance was 5 mm and the friction ball was a stainless steel ball.
[0048] Table 1
[0049]
[0050] The surface treated tool of Example 1 was taken for morphology observation: the cross section of the composite coating was observed by FEISirion IMP (scanning electron microscope), as shown in FIG. Figure 2 As shown; the wear scars of the samples after the friction coefficient test were observed using an ultra-depth of field microscope, as shown Figure 3 As shown, by observing the peeling marks of the coating on both sides of the wear mark, it can be seen that the coating does not fall off in blocks, but changes from deep to shallow, which shows that the bonding force between the coatings is good and it is not easy to fall off. By comparing the composite coating of Example 1 with Comparative Example 1 and Comparative Example 2, the composite coating has a higher hardness (29.52GPa) and a lower friction coefficient (0.11), and the mass loss after 30 minutes of wear is 1mg.
[0051] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high entropy composite coating for cemented carbide tools, characterized in that: The coating comprises a high entropy alloy FeCoCrNiMn layer coated on the surface of the tool and a high entropy alloy boride layer coated on the surface of the high entropy alloy FeCoCrNiMn layer; The high entropy composite coating for cemented carbide tools is prepared by the following steps: 1) Pre-treat the surface of the carbide tool matrix to increase the bonding force: 2) After screening and drying the high entropy alloy FeCoCrNiMn powder; heating the cemented carbide tool substrate to a preset temperature; the composition of the high entropy alloy FeCoCrNiMn powder includes Fe: 50-60%, Co: 10-20%, Cr: 10-15%, Ni: 10-15%, Mn: 10-20% by mass percentage; 3) Under a protective atmosphere, high entropy alloy FeCoCrNiMn powder is used as welding powder to perform surfacing welding on the cemented carbide tool substrate. After surfacing welding, the tool substrate is placed in a heat preservation medium to cool down, that is, a high entropy alloy FeCoCrNiMn layer is formed on the surface of the cemented carbide tool substrate; 4) pre-treating the surface of the tool substrate with the cladding high entropy alloy FeCoCrNiMn layer obtained in step 3) to increase the bonding strength; 5) Boron iron alloy and silicon carbide are mixed evenly in a mass ratio of 1:12-20 as a penetrant, and under a set vacuum degree and protective atmosphere, the tool substrate with the cladding high entropy alloy FeCoCrNiMn layer is kept at 800-1200°C for 8-10h for boronizing; after the boronizing is completed, it is quenched and cooled to room temperature, and then the temperature is increased for tempering to form a high entropy alloy boride layer on the surface.
2. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 1, characterized in that: The composition of the high entropy alloy FeCoCrNiMn layer includes, by mass percentage, Fe: 50-60%, Co: 10-20%, Cr: 10-15%, Ni: 10-15%, and Mn: 10-20%; the raw materials of the high entropy alloy boride layer include silicon carbide and ferroboride, wherein the mass ratio of ferroboride to silicon carbide is 1:12-20.
3. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 2, characterized in that: The thickness of the high entropy alloy FeCoCrNiMn layer is 1.0-2.0 mm; the thickness of the high entropy alloy boride layer is 20-30 μm.
4. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 3, characterized in that: The composition of the high entropy alloy FeCoCrNiMn layer includes, by mass percentage, Fe: 55.8%, Co: 11.2%, Cr: 10.9%, Ni: 10.2%, and Mn: 11.9%; the raw materials of the high entropy alloy boride layer include silicon carbide and ferroboron alloy, wherein the mass ratio of ferroboron alloy to silicon carbide is 1:15; the thickness of the high entropy alloy FeCoCrNiMn layer is 2.0 mm; the thickness of the high entropy alloy boride layer is 21.35 μm.
5. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 1, characterized in that: In the step 3), a plasma arc surfacing method is used for surfacing welding by a plasma surfacing machine, and a linear reciprocating welding is set as the surfacing path, with a speed of 800-1200 mm / min, a reciprocating number of times of 10-18 times, and a surfacing arc current of 50-70A.
6. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 5, characterized in that: In the step 3), the powder feeding flow rate of the welding powder is 1.5-2.5 L / min.
7. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 5, characterized in that: In the step 3), the weld between the tool substrate and the high entropy alloy FeCoCrNiMn layer is processed by continuous welding during the surfacing process, and the weld length is set to 40-60 mm and the weld width is set to 2-4 mm.
8. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 5, characterized in that: In the step 3), a safety distance of 1-5 mm is reserved between the operating table of the plasma welding machine and the tool base; the overlap rate is set to 30-60%, and the nozzle and the tool base are 10-18 mm apart.
9. The method for preparing a high entropy composite coating for cemented carbide tools according to claim 1, characterized in that: In the step 5), the annealing temperature is 400-450° C. and the duration is 3-4 hours.
Citation Information
Patent Citations
High-performance NiCoCrFeMnTi system high-entropy alloy and preparation method thereof
CN107686928A
Preparation method of boronizing layer on surface of high-entropy alloy
CN109554660A